Unusual Tibial Site Metastases from a Muscle Invasive Urothelial Carcinoma: A Rare Case Report - G., Kastanis; M., Bachlitzanaki; A., Pantouvaki; G., Magarakis; M., Spyrantis (International Journal of Innovative Research in Medical Science, 2020)
Bladder cancer is a common malignancy of genitourinary tract with a considerable morbidity and mortality. Muscle invasive urothelial carcinoma is the most common type of cancer especially in ages over 65 years old. Though various metastases have been observed, bone localization is the second site metastases and is appeared in pelvis and spine. We present a case with tibial diaphyseal bone metastases from urothelial carcinoma as a rare manifestation and we review the literature among diagnoses and therapeutic management.